Factors Affecting Cadres’ Knowledge and Ability to Identify Breastfeeding Problems in Malang District - Wati, Linda Ratna; Indahwati, Lilik; Putri, Rismaina; Jannah, Miftahul; Windari, Era Nurisa; Hanifarizani, Rahma Dian (Universitas Andalas, 2024)
Background: Breast milk is the ideal nutrient to support the growth and development of the baby. The government strives to increase exclusive breastfeeding, one of which is through the empowerment of cadres, so intensive efforts are needed to optimize the role of cadres in supporting exclusive breastfeeding. Objectives: This study aims to analyze factors related to the knowledge and ability of cadres in identifying breastfeeding problems. Methods: The research design used observational analytic with a cross-sectional approach. A total of 46 posyandu cadres in the Malang Regency area were involved in this research. Bivariate analysis using Spearman’s correlation with SPSS software version 26 and multivariate using path analysis with Smartpls software version 3. Results: The cadres' knowledge related to breast milk and breastfeeding is mostly sufficient (65.22%). The ability of cadres to identify the breastfeeding problems the most in the category is sufficient (63.04%). The pathway analysis showed that the factors that influenced knowledge were education (r=0.488) and breastfeeding experience (r=0.336), but age had a negative effect (r=-0.267). Factors that influenced the ability to identify breastfeeding problems were breastfeeding experience (r=0.542) and breastfeeding training history (r=0.469). Conclusions: Education and age are important factors in the recruitment of cadres, in addition, information and practices related to breast milk and breastfeeding obtained through experience and training are also needed to support exclusive breastfeeding.